Construction of a potentially functional long noncoding RNA-microRNA-mRNA network in diabetic cardiomyopathy - Qiwen Cao; Zhihui Dong; Yangbo Xi; Jiana Zhong; Jianzhong Huang; Qunfeng Yang (Journal of Research in Medical Sciences)
Background: Diabetic cardiomyopathy (DCM) is a severe complication among patients with Type 2 diabetes, significantly increasing heart failure risk and mortality. Despite various implicated mechanisms, effective DCM treatments remain elusive. This study aimed to construct a comprehensive competing endogenous RNA (ceRNA) network in DCM using bioinformatics analysis. Materials and Methods: Three expression profiles datasets (GSE161827, GSE161931, and GSE241166) were collected from gene expression omnibus database and then integrated for the identification of differentially expressed genes (DEGs). Gene Ontology, Kyoto Encyclopedia of Gene and Genome pathway analysis, and Gene set enrichment analysis (GSEA) were employed for functional analysis. Protein-protein interaction (PPI) network and hub genes were also identified. The ceRNA regulatory networks were constructed based on interaction between long noncoding RNA (lncRNA) and DEGs, microRNA (miRNA) and DEGs, as predicted by public available databases. Results: A total of 105 DEGs, including 44 upregulated and 61 downregulated genes were identified to be associated with DCM. Functional enrichment analysis showed that fatty acid metabolism pathway and inflammatory responses were significantly enriched in DCM. A total of 56 interactions between miRNA with DEGs, and 27 interactions between lncRNA with miRNA was predicted. Besides, a ceRNA network includes 9 mRNA, 17 miRNA and 10 lncRNA was constructed, among which Cdh20 and Cacna2d2 were hub genes in PPI network. Conclusion: The identified hub genes and ceRNA network components provide valuable insights into DCM biology and offer potential diagnostic biomarkers and therapeutic targets for further investigation. Further experimental validation and clinical studies are warranted to translate these findings into clinical applications.